Influence of advanced pulmonary vascular remodeling on accuracy of echocardiographic parameters of left ventricular filling pressure. (1st January 2021) - Chiba, Yasuyuki; Iwano, Hiroyuki; Kaga, Sanae; Shinkawa, Mio; Murayama, Michito; Ohira, Hiroshi; Ishizaka, Suguru; Sarashina, Miwa; Tsujinaga, Shingo; Yokoyama, Shinobu; Nakabachi, Masahiro; Nishino, Hisao; et al.
Abstract : Evaluation of left ventricular filling pressure plays an important role in the clinical management of pulmonary hypertension. However, the accuracy of echocardiographic parameters for the determination of left ventricular filling pressure in the presence of pulmonary vascular lesions has not been fully addressed. We retrospectively investigated 124 patients with pulmonary hypertension due to pulmonary vascular lesions (noncardiac pulmonary hypertension group) and 113 patients with ischemic heart disease (control group) who underwent right heart catheterization and echocardiography. The noncardiac pulmonary hypertension group was subdivided into less‐advanced and advanced groups according to median pulmonary vascular resistance. Pulmonary artery wedge pressure was determined as left ventricular filling pressure. As echocardiographic parameters of left ventricular filling pressure, the ratio of early‐ (E) to late‐diastolic transmitral flow velocity (E/A), ratio of E to early‐diastolic mitral annular velocity (E/e′), and left atrial volume index were measured. In the less‐advanced noncardiac pulmonary hypertension and control groups, positive correlations were observed between pulmonary artery wedge pressure and late‐diastolic transmitral flow velocity ( R = 0.41, P = 0.002 and R = 0.71, P < 0.001, respectively) and left atrial volume index ( R = 0.53, P < 0.001 and R = 0.41, P < 0.001), whereas in the advanced noncardiac pulmonary hypertension group, pulmonary artery wedge pressure was only correlated with left atrial volume index ( R = 0.27, P = 0.032). In the controls, only pulmonary artery wedge pressure determined E (β = 0.48, P < 0.001), whereas both pulmonary artery wedge pressure and pulmonary vascular resistance were independent determinants of E (β = 0.29, P < 0.001 and β = –0.28, P = 0.001, respectively) in the noncardiac pulmonary hypertension group. In conclusion, in the presence of advanced pulmonary vascular lesions, conventional echocardiographic parameters may not accurately reflect left ventricular filling pressure. Elevated pulmonary vascular resistance would lower the E, even when pulmonary artery wedge pressure is elevated, resulting in blunting of echocardiographic parameters for the detection of elevated left ventricular filling pressure.